Insulin Analogs Revisited - Eckel, J. (Current Medicinal Chemistry - Immunology, Endocrine & Metabolic Agents, 2005)
Insulin analogs have largely replaced conventional insulin preparations and extensive clinical studies have confirmed the beneficial action profile of these artificial insulin molecules. Tight blood sugar control is a major goal of intensified insulin therapy and this can be obtained much more efficiently when using insulin analogs. Currently, three rapidacting insulin analogs are in clinical use based on either a change of the amino acid sequence (insulin lispro) or exchanges of one (insulin aspart) or two (insulin glulisine) amino acids. Insulin glargine was the first long-acting insulin analog with a well documented low risk of nocturnal hypoglycemia. Insulin detemir is the most recent insulin analog with a longacting profile based on esterification with a fatty acid. For all insulin analogs safety considerations are mandatory and must take into account both the IGF-I and the insulin receptor. Enhanced mitogenic activity and a tumorigenic potential of an insulin analog may involve increased IGF-I receptor signaling and/or sustained insulin receptor activation. Both insulin and IGF-I receptors are involved in the regulation of tumor cell growth. Further, insulin/IGF-hybrid receptors are abundant in these cells and additional studies will be needed to assess the role of these receptors in the long-term action profile and safety of insulin analogs.
Keywords: insulin receptor